Motif 'Because Of' dan 'In Order To' Pemuda Dalam Pengembangan Rumah Spot Wisata di Kampung Kayutangan Kota Malang - Dina Daratirta (Brawijaya Journal of Social Science, 2024)
This research explores the motives of youth in the development of tourist spot houses in Kayutangan Tourism Village, Malang City. The focus of the research is the commodification of ancient houses into coffee shops and the experience of youth in entrepreneurship. The problem was analyzed using Alfred Schutz's motive theory, namely because of motive and in order to motive. The role of youth in the development of tourist spot houses in Kayutangan Village is seen through past motives and goals that encourage, and want to be achieved by youth in commodifying houses into coffee shops. The research approach was conducted using Alfred Schutz's qualitativephenomenological method. Data collection was obtained through the author's first visit to make observations followed by an interview process, as well as documentation of previous research. Determination of informants was done by purposive sampling. The results showed that the presence of tourists as a background to open a coffee shop, in line with the concept of because of motive. The main purpose of such commodification is to increase income, which is considered an in order to motive because it is oriented towards future expectations. The result also found that youth play an important role in managing the shop. The youth showed a willingness to contribute to tourism development. One of them is a young man who just graduated from senior high school (SMA) has an entrepreneurial spirit that shows concern and sensitivity to be actively involved in tourism development. The desire to maintain tourism is the impetus for youth to get involved. The form of involvement is not only to promote tourism, but also to fulfill the needs of tourists. The suggestions generated from this research emphasize the need to strengthen collaboration between youth and Pokdarwis, through training toimprove the capabilities of young entrepreneurs in developing businesses. ABSTRAK Penelitian ini mengeksplorasi motif dan pengalaman melalui kapabilitas pemilik rumah kuno dalam pengembangan wisata berbasis komunitas (Community Based Tourism) di Kampung Wisata Kayutangan, Kota Malang. Fokus penelitian adalah aktivitas komodifikasi rumah kuno menjadi kedai kopi, serta pengalaman pemuda dalam berwirausaha. Analisis permasalahan dengan kajian teori motif oleh Alfred Schutz, yaitu because of motive (sebab) dan in order to motive (tujuan) melalui pendekatan penelitian kualitatif-fenomenologi. Kapabilitas pemilik rumah kuno dalam pengembangan wisata berbasis CBT di Kampung Kayutangan dilihat melalui motif masa lalu dan tujuan yang mendorong serta ingin dicapai oleh mereka dalam mengomodifikasi rumah menjadi kedai kopi. Pengumpulan data diperoleh melalui metode: dokumentasi observasi, dan wawancara. Penentuan informan dilakukan secara purposive sampling. Hasil penelitian menunjukkan bahwa kapabilitas pemilik rumah kuno terletak pada kemampuan dalam mengkomodifikasi rumah untuk menarik wisatawan. Kehadiran wisatawan sebagai latar belakang untuk membuka kedai kopi, sejalan dengan konsep because of motive. Tujuan utama dari komodifikasi tersebut adalah untuk meningkatkan pendapatan, yang dianggap sebagai in order to motive karena berorientasi pada harapan masa depan. Penelitian ini juga menemukan bahwa pemuda memainkan peran penting dalam mengelola kedai. Pemuda menunjukkan kemauan untuk berkontribusi dalam pengembangan pariwisata. Salah satu dari mereka adalah seorang pemuda yang baru lulus Sekolah Menengah Atas (SMA) telah memiliki jiwa kewirausahaan menujukkan kepedulian serta kepekaan untuk terlibat aktif dalam pengembangan pariwisata. Keinginan untuk mempertahankan pariwisata menjadi dorongan dalam diri pemuda untuk terlibat. Bentuk keterlibatan pun tidak hanya sekedar mempromosikan wisata, tetapi juga diiringi akan pemenuhan kebutuhan wisatawan. Saran yang dihasilkan dari penelitian ini menekankan perlunya penguatan kolaborasi antara pemuda dan Pokdarwis, melalui pelatihan untuk meningkatkan kapabilitas pengusaha muda dalam mengembangkan usaha.